To evaluate the efficacy of ropivacaine with dexmedetomidine and ropivacaine with dexamethasone in fascia iliaca compartment block for post-operative pain relief in fracture femur surgeries: A comparative randomized study - Bansal, Sakshi; Neelima Tandon; Manmohan Jindal; Namrata Jain (Asian Journal of Medical Sciences, 2023)
Background: Patients with femur fracture experience severe post-operative pain. Fascia iliaca compartment block (FICB) is a safe and effective approach for providing post-operative analgesia. Aims and Objectives: The aim of the study was to compare the post-operative pain relief with dexmedetomidine and dexamethasone with ropivacaine in FICB. Materials and Methods: This prospective, double-blinded, randomized controlled, and clinical study was done on 105 patients, with ASA physical status I-II, aged between 18 and 70 years, undergoing surgery for femur fracture. Patients were randomly allocated into three groups. All patients received FICB by landmark technique before spinal anesthesia. Group A patients received 38 mL of 0.25% ropivacaine and dexmedetomidine, Group B received 38 mL of 0.25% ropivacaine and dexamethasone and Group C received 38 mL of 0.25% ropivacaine. Patients were assessed for analgesia during positioning and post-operative period using visual analog scale (VAS). Hemodynamic parameters and time for first rescue analgesia were recorded. Results: The mean VAS score at 6 h after surgery was 0.74±0.95 in Group A, in Group B 2.26±0.95, and in Group C was 4.23±1.17, which was statistically significant (P<0.05). The time for first rescue analgesia was 13.03±1.79 h in Group-A, 8.31±1.11 h in Group B and 5.94±0.87 h in Group C (P<0.001). Conclusion: Addition of dexmedetomidine or dexamethasone to ropivacaine for FICB in femur fracture patients prolongs post-operative analgesia compared to ropivacaine alone.